ANALISA CRITICAL CONTROL POINT (CCP) PADA PRODUKSI IKAN KALENG DI PT. PERMATA BAHARI MALINDONESIA: Analisys of Critical Control Point (CCP) on Canned Fish Production at PT. Permata Bahari Malindonesia - Moh.Rizki Aziz, Rosiana Ulfa, Bagus Setyawan (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2021)
Food quality is the main key to improving the safety of food products. Consumers today are smarter in choosing food products, the food quality assurance logo is a benchmark that influences purchases. The concept of food quality control has changed, from initially only analyzing the final product to product analysis at every critical stage of its processing. Hazard Analysis Critical Control Point (HACCP) is one method to identify each critical point in the processing process. The purpose of this fieldwork practice is to know, study, understand, and analyze Hazard Analysis Critical Control Point HACCP which has been apply at the fish canning process at PT. Permata Bahari Malindonesia. This study uses a survey method, primary data is collected through observation, documentation, interviews and direct participation in lemuru fish canning activities. The result obtained from this study is that PT. Permata Bahari Malindonesia implements GMP, SSOP, and traceability in each canning process as the basic feasibility of implementing HACCP.